Case ReportMicrocytic anaemia as the clinical manifestation of coeliac disease in an adult patient: case report - Barczyńska, Tacjana; Graczyk, Małgorzata; Kremplewska-Należyta, Elżbieta; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Coeliac disease is a chronic inflammatory disorder of the small intestine caused by permanent gluten intolerance. It may develop in patients of any age with genetic predispositions. Advanced age in patients with undiagnosed and untreated coeliac disease increases difficulties in establishing a correct diagnosis, because symptoms in the gastrointestinal system become less pronounced than those in other organs. For example, hypoferric anaemia may be the only symptom of coeliac disease, or it may develop long before the fully symptomatic disease. This paper presents a case report on a 47-year-old female patient with anaemia, thrombocytopenia and weight loss, in which coeliac disease was diagnosed during hospitalization at the Clinic of Allergic Diseases, Clinical Immunology and Internal Diseases of L. Rydygier’s Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University, Toruń. The paper also presents a discussion on aetiopathogenesis, main symptoms, diagnostic criteria and management principles for coeliac disease.